Food choices and eating habits of Indian migrants in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science degree in Nutrition and Dietetics at Massey University, Albany, New Zealand - Mushtaq Ahmed, Ayesha (Massey University, 2023)
Background: The migration of Indians is documented from 1769 to the present day in New Zealand. Migrants have been shown to provide significant support to the New Zealand economy and add cultural diversity to the country. The data from 2022 showed 4773 Indians migrants moved to New Zealand. Moving to a new country has certain challenges including housing, work, education, and health. In addition, there may be influences on dietary behaviour. Aim: This study aims to understand the factors influencing the food choices and eating habits of Indian migrants in New Zealand. Methods: This study consisted of two phases: (1) semi-structured interviews with 11 participants and (2) a questionnaire survey based on the findings of phase one explored how multiple levels influenced food choices and eating behaviour in 110 participants. Results: In the study, it was found that higher food prices did not necessarily reflect the quantity and that ethnic foods were easier to access in urban areas, whereas religious and cultural factors heavily influenced food choices, while cooking skills also played a significant role. Those living with their partners or belonging to the same culture exhibited better eating habits. Long working hours including shift work was seen to influence the reliance on takeaways and poor eating habits. However, participants were generally open to adopting healthier lifestyles and exploring different food cultures. Conclusion: The study found that factors influencing food choices were present across all levels of the ecological model for health promotion. The findings suggest that interventions must be comprehensive and address multiple levels of influence to be effective. Interventions that focus on only one level, or one factor, are likely to be ineffective. Additionally, interventions should be tailored to address the specific needs of the individual. According to the study, food choices and dietary patterns need to be viewed holistically. In addition to reducing barriers to these diets, interventions should increase access to healthy foods. Educating and motivating individuals about healthy eating options should also be undertaken as part of public health initiatives.
Keywords: 321004 Nutritional science